Clinical Treatment Experience in Severe and Critical COVID-19. (30th September 2021) - Li, Mingliang; Zhu, Donglin; Yang, Jianghua; Yan, Ling; Xiong, Zhiyong; Lu, Jiahai; Bi, Xiaogang; Xi, Yun; Chen, Zeliang
Abstract : Compared with other deadly diseases, the coronavirus disease 2019 (COVID-19) is highly infectious with a relatively low mortality rate. Although critical cases account for only 5% of cases, the mortality rate for the same is nearly 50%. Therefore, the key to the COVID-19 treatment is to effectively treat severe patients and reduce the transition from severe to critical cases. A retrospective study was carried out to evaluate outcomes of treatment in patients with severe and critical COVID-19 admitted to a COVID-19 special hospital in Wuhan, China. A total of 75 severe and critical COVID-19 patients were admitted and treated with immunomodulation as the main strategy combined with anti-inflammatory therapy and appropriate anticoagulation. Leukocyte levels in patients with 7-14 days of onset to diagnosis were significantly lower than in those with >14 days. Higher levels of globulin and D-dimer and lower lymphocyte levels were found in the older age group (>65 years) than in the middle-aged group (50-64 years). Patients with comorbidity had higher levels of inflammatory indicators. After treatment, 65 (86.67%) patients were cured, 7 (9.33%) had improved, and 3 (4.00%) had died. Median hospitalization duration was 23 days. Fatal cases showed continuously increased levels of globulin, dehydrogenase (LDH), hypersensitive C-reactive protein (hs-CRP), D-dimer, and cytokines during treatment. Time from onset to diagnosis, age, and comorbidity are important influencing factors on treatment effects. The occurrence of immunosuppression, "cytokine storm, " and thrombosis may be an important cause of death in severely infected cases. In conclusion, high cure rate and low mortality suggested that immunomodulation combined with anti-inflammatory therapy and appropriate anticoagulant therapy is a good strategy for treatment of patients with severe and critical COVID-19.